BUILDING INFORMATION MODELING: FINANCIAL AND ACCOUNTING ASPECT (World of finance, 2024)
Introduction. The implementation of building information modeling (BIM) technology is a promising direction in the development of the construction enterprise management system. It is advisable to use BIM technology also for economic purposes, which requires the study of financial and accounting features of the construction process in the conditions of digitization of management.The purpose of the article is to research the financial and accounting aspects of the use of building information modeling technology to optimize the management of construction enterprises.Results. The possibility of positioning individual construction objects (premises, floors, spatial zones) by operational centers of responsibility under the conditions of using BIM technology, which is the basis for the formation of a cluster structure of accounting and management of construction enterprises, is substantiated. The cluster is proposed to recognize a differentiated building object, which is an operational center of responsibility, which is in close relationship with various functional centers of responsibility and other clusters. The importance of positioning centers of responsibility simultaneously as centers of investments, incomes and expenses in the conditions of using BIM technologies, which involves a positive transformation of the method of processing financial and accounting information, is proven. In order to expand the functionality of the software for BIM purposes, the perspective of its improvement has been substantiated in the direction of: predicting options for forming planned estimates of construction costs with the adjustment of normative and actual costs; expansion of non-capital construction accounting methods; developing a procedure for assessing the damage caused by military actions in order to plan the need for financial resources for the restoration of destroyed or damaged buildings. In order to organize an effective information exchange between the participants of the construction process, it is necessary to ensure information synchronization between software for BIM design, accounting and management software products, electronic systems of business communications and electronic government.Conclusions. Expanding the functional and information capabilities of BIM technologies in terms of taking into account the financial and accounting aspects of construction, as well as ensuring information synchronization with current electronic services and document management systems, contributes to the formation of the newest concept of innovative smart construction.